DUKUNGAN BIDAN DALAM MENINGKATKAN BREASTFEEDING SELF EFFICACY MASA AWAL LAKTASI - Ina Handayani; Elin Supliyani (JURNAL RISET KESEHATAN POLTEKKES DEPKES BANDUNG, Online ISSN 2579-8103, 2021)
Breastfeeding failure occurs more frequently in the first days after delivery. This happens because of the low milk production in the first days. Midwife support from pregnancy to early lactation can increase breastfeeding self-efficacy, which is a person's belief in his ability to successfully breastfeed his baby. The existence of good knowledge, this knowledge will change the mindset of previous experiences, mothers can apply effective breastfeeding techniques and create conducive emotional conditions. The research design used pre-experimental design, with one group pre-test post-test. Sampling using non-probability sampling techniques, purposive sampling method according to inclusion criteria, there are 29 mothers with a history of breastfeeding failure. The instrument used Breastfeeding Self-Efficacy Scale Form (BSESF). The intervention carried out in this study was the provision of midwife support in the form of an educational pattern from the 3rd trimester of pregnancy until 7 days postpartum, then evaluated the increase in Breastfeeding self-efficacy both before and after the intervention. The research analysis design used  Wilcoxon test. The results showed that the value of the Breastfeeding self-efficacy score increased with the median value before the intervention of 50 and after the intervention of 61 (p <0.05). There is an effect of midwife support in increasing breastfeeding self-efficacy during early lactation in mothers with a history of failure to provide exclusive breastfeeding. It is suggested that this research can be applied to improve the success of breastfeeding, especially in breastfeeding in the early postpartum period.